The American Civil War and black colonization - Page, S; Sebastian Nicholas Page (2012)
This is a study of the pursuit of African American colonization as a state and latterly a federal policy during the period c. 1850-65. Historians generally come to the topic via an interest in the Civil War and especially in Lincoln, but in so doing, they saddle it with moral judgment and the burden of rather self-referential debates. The thesis argues that, whilst the era’s most noteworthy ventures into African American colonization did indeed emerge from the circumstances of the Civil War, and from the personal efforts of the president, one can actually offer the freshest insights on Lincoln by bearing in mind that colonization was, above all, a real policy. It enjoyed the support of other adherents too, and could be pursued by various means, which themselves might have undergone adjustment over time and by trial and error. Using an array of unpublished primary sources, the study finds that Lincoln and his allies actively pursued colonization for a longer time, and with more persistence in the face of setbacks, than scholars normally assume. The policy became entangled in considerations of whether it was primarily a domestic or an international matter, whilst other overlapping briefs also sabotaged its execution, even as the administration slowly learned various lessons about how not to go about its implementation.By early 1864, the resulting confusion, as well as the political fallout from the fiasco of the one expedition to go ahead, curtailed the president’s ability to continue with the policy. There are strong suggestions, however, that he had not repudiated colonization, and possibly looked to revive it, even as he showed a tentative interest in alternative futures for African Americans. This thesis makes a case against unrealistically binary thinking, anachronistic assumptions, abused hindsight, sweeping interpretive frameworks, and double standards of evidentiary assessment respecting a technically imperfect and ethically awkward policy.